Malariometric Survey Among Elementary School Children Aged 6-9 Years in Sangihe Besar - Laurentz R.; Paul S. Manoempil (Indonesian Pediatric Society, 1996)
One of the most common classification of malaria transmission in particular area is based on the levels of endemicity. It could be quantified by determination of chilÂdren with enlarged spleens and parasitemia. A